Targeted Inhibition of Aggrecanases Prevents Articular Cartilage Degradation and Augments Bone Mass in the STR/Ort Mouse Model of Spontaneous Osteoarthritis. Issue 4 (14th February 2019) - Kanakis, Ioannis; Liu, Ke; Poulet, Blandine; Javaheri, Behzad; van 't Hof, Rob J.; Pitsillides, Andrew A.; Bou‐Gharios, George
Abstract : Objective: Cartilage destruction in osteoarthritis (OA) is mediated mainly by matrix metalloproteinases (MMPs) and ADAMTS. The therapeutic candidature of targeting aggrecanases has not yet been defined in joints in which spontaneous OA arises from genetic susceptibility, as in the case of the STR/Ort mouse, without a traumatic or load‐induced etiology. In addition, we do not know the long‐term effect of aggrecanase inhibition on bone. We undertook this study to assess the potential aggrecanase selectivity of a variant of tissue inhibitor of metalloproteinases 3 (TIMP‐3), called [‐1A]TIMP‐3, on spontaneous OA development and bone formation in STR/Ort mice. Methods: Using the background of STR/Ort mice, which develop spontaneous OA, we generated transgenic mice that overexpress [‐1A]TIMP‐3, either ubiquitously or conditionally in chondrocytes. [‐1A]TIMP‐3 has an extra alanine at the N‐terminus that selectively inhibits ADAMTS but not MMPs. We analyzed a range of OA‐related measures in all mice at age 40 weeks. Results: Mice expressing high levels of [‐1A]TIMP‐3 were protected against development of OA, while those expressing low levels were not. Interestingly, we also found that high levels of [‐1A]TIMP‐3 transgene overexpression resulted in increased bone mass, particularly in females. This regulation of bone mass was at least partly direct, as adult mouse primary osteoblasts infected with [‐1A]TIMP‐3 in vitro showed elevated rates of mineralization. Conclusion: The results provide evidence that [‐1A]TIMP‐3–mediated inhibition of aggrecanases can protect against cartilage degradation in a naturally occurring mouse model of OA, and they highlight a novel role that aggrecanase inhibition may play in increased bone mass.